BMI, WAIST CIRCUMFERENCE, VITAMIN D INTAKE , AND CALCIUM INTAKE IN RELATION TO HYPERTENSION AMONG MENOPAUSAL WOMEN IN BANDUNG - Nurrafina Gunawan, Nisrina; Saliha Puspita Prameswari, Fajria; Fauza, Ahdiyatul; Santanu, Ayu Mutiara (Jurnal Gizi dan Pangan Soedirman, 2025)
Menopausal women are more vulnerable to hypertension due to hormonal changes, particularly the decline in estrogen. This vulnerability is further increased by lifestyle-related factors such as excess body weight, abdominal fat, and inadequate nutrient intake.Menopause and hypertension are prevalent health issues in Bandung, yet studies examining how body mass index (BMI), waist circumference, vitamin D intake, and calcium intake affect the risk of hypertension remain limited. This study was conducted to address that gap. To examine the relationship between BMI, waist circumference, vitamin D intake, and calcium intake with the occurrence of hypertension among menopausal women in Bandung. A cross-sectional study was carried out from January to March 2025 among 70 menopausal women aged 45–60 years in Sukajadi District, Bandung. Data were obtained through interviews, anthropometric measurements, blood pressure assessments, and dietary evaluations using a semi-quantitative food frequency questionnaire (SQ-FFQ). Associations were analyzed using the Chi-square test. Hypertension was significantly associated with BMI (OR=11.27; p<0.05), waist circumference (OR=7.85; p<0.05), and low vitamin D intake (OR=9.67; p<0.05). Calcium intake showed no significant association. Excess weight and low vitamin D intake are major contributors to hypertension among menopausal women. Preventive strategies focusing on weight control and sufficient nutrient intake are essential.